2019
DOI: 10.3122/jabfm.2019.06.190168
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Understanding of Hair Care Maintenance as a Barrier to Physical Activity in African American Women

Abstract: Introduction: African American (AA) women have reported hair maintenance as a barrier to regular exercise; however, to our knowledge, this study is the first to identify primary care provider thoughts, attitudes, beliefs, and knowledge regarding hair as a barrier to increased physical activity among AA females. Methods: A 13-question electronic survey was sent via email to 151 clinicians working within a department of family medicine's 8 ambulatory clinics within a large urban academic medical center. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Healthcare providers need to encourage PA among their patients at risk, although sex-and racial/ethnic-specific barriers to PA should be considered in order to increase engagement. For example, a small body of research has identified hair care as a significant obstacle among Black women, with responders reporting "sweating out my hairstyle" as a barrier to PA (32)(33)(34). Other literature among a group of Latina women reported that caregiving, family obligations, child care, and lack of relatives to help with child care were barriers to exercise (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers need to encourage PA among their patients at risk, although sex-and racial/ethnic-specific barriers to PA should be considered in order to increase engagement. For example, a small body of research has identified hair care as a significant obstacle among Black women, with responders reporting "sweating out my hairstyle" as a barrier to PA (32)(33)(34). Other literature among a group of Latina women reported that caregiving, family obligations, child care, and lack of relatives to help with child care were barriers to exercise (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlighted some socio‐cultural issues influencing PA for health, with reference to cultural norms for females within Arabic cultures 78,94 . In African American populations, Tolliver et al 97 . highlighted that hair care in female populations was a barrier to PA.…”
Section: Methodsmentioning
confidence: 99%
“…30,78,94,95 These studies highlighted some socio-cultural issues influencing PA for health, with reference to cultural norms for females within Arabic cultures. 78,94 In African American populations, Tolliver et al 97 highlighted that hair care in female populations was a barrier to PA. Given the increasing globalisation of the world, with increasing socio-cultural diversity, further research exploring culture-specific barriers to PA for health is required.…”
Section: Societal Factorsmentioning
confidence: 99%
“…El hábito de alisar el cabello crespo probablemente comenzó durante el período de la esclavitud, cuando las mujeres negras usaban materiales grasos y, a veces, resinas vegetales para alisar su cabello. A mediados de 1900, Sarah Breedlove (más tarde conocida como Madame C. J. Walker), una mujer afroamericana, creó un ungüento compuesto por varios aceites y revolucionó el peinado del cabello crespo (52,53) .…”
Section: Consideraciones Cosméticas E Históricasunclassified
“…Lora, L; Gómez, MB; Da Cruz, K las afroamericanas en comparación con las mujeres blancas. Entre esta población, el uso de tintes para el cabello de tonos oscuros se asoció con un mayor riesgo de cáncer de mama (52,57) . Recientemente la industria cosmética ha invertido esfuerzos en el estudio de este tipo de cabellos en busca de entender mejor y adaptar cosméticos en el mismo sentido (58) .…”
Section: Consideraciones Cosméticas E Históricasunclassified